2016
DOI: 10.1371/journal.pntd.0004340
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Oxidized Proteins in Entamoeba histolytica by Resin-Assisted Capture: Insights into the Role of Arginase in Resistance to Oxidative Stress

Abstract: Entamoeba histolytica is an obligate protozoan parasite of humans, and amebiasis, an infectious disease which targets the intestine and/or liver, is the second most common cause of human death due to a protozoan after malaria. Although amebiasis is usually asymptomatic, E. histolytica has potent pathogenic potential. During host infection, the parasite is exposed to reactive oxygen species that are produced and released by cells of the innate immune system at the site of infection. The ability of the parasite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 85 publications
6
85
0
Order By: Relevance
“…According to previous reports in mammalian cells, the cysteines in actin are some of the most susceptible targets of oxidation and nitrosylation and their modification is the likely cause of reduced polymerization activity and altered binding of actin with actin binding proteins45. We have previously reported that a number of cysteine residues in E. histolytica actin are susceptible to oxidation in oxidatively stressed trophozoites20 and to S-nitrosylation in NAT (manuscript in preparation). Based on this information, it is tempting to speculate that the upregulation of cytoskeletal proteins in NAT is a mechanism used by the parasite to replace SNO cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…According to previous reports in mammalian cells, the cysteines in actin are some of the most susceptible targets of oxidation and nitrosylation and their modification is the likely cause of reduced polymerization activity and altered binding of actin with actin binding proteins45. We have previously reported that a number of cysteine residues in E. histolytica actin are susceptible to oxidation in oxidatively stressed trophozoites20 and to S-nitrosylation in NAT (manuscript in preparation). Based on this information, it is tempting to speculate that the upregulation of cytoskeletal proteins in NAT is a mechanism used by the parasite to replace SNO cytoskeletal proteins.…”
Section: Discussionmentioning
confidence: 89%
“…We have recently showed that the accumulation of the polyamine putrescine and E. histolytica ’s resistance to OS are linked20. The synthesis of polyamines has been also linked to NS resistance in bacteria2122.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are strongly acidic proteins that are commonly found on the surface of the ribosome in all organisms [40]. Eukaryotic 60 s acidic ribosomal proteins are called ribosomal P proteins because they can be phosphorylated [41]. P protein is a structural constituent of the ribosome and is involved in nucleic acid binding and translation.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are also consistent with the observation that protein biosynthesis is inhibited during oxidative stress in E . histolytica [25]. It has been suggested that oxidation of components of the parasite’s translation machinery (e.g., ribosomal proteins, elongation factors) [25], and enzymatic down-regulation of almost all tRNA species [31] are responsible for reduced protein biosynthesis during H 2 O 2 exposure.…”
Section: Discussionmentioning
confidence: 99%